Perception of selected chief executives in the Province of Iloilo on graft and corruption and on the Office of the Ombudsman. - Rivera, Florence Joyce
This study determines the perception of selected local chief executives (municipal mayors) of Iloilo Province on graft and corruption and on the Office of the Ombudsman and its policies, programs, and performance. Data is gathered through the use of interview schedule on questionnaire and respondents are selected through simple random samplingusing the lottery technique. The findings of the study show that the municipal mayors of Iloilo Province are often inconsistent in their perceptions and beliefs on graft and corruption. Furthermore, most of the respondents perceive the Office of the Ombudsman as unresponsive and incompetent in the performance of their duties and lacking in integrity. However, the Ombudsman's graft watch programs (creation of Corruption Prevention Units and Junior Graft Watch Units) received positive responses from the respondents. Perception is an integral factor that may affect a person's behavior and attitude. The perceptions of local chief executives on graft and corruption and on the Office of the Ombudsman determine the way in which these respondents react or behave towards the phenomena and to the very instituion that is amndated to fight and prevent it.